EMPLOYABILITY OF YOUNG WOMEN GRADUATES IN CÔTE D'IVOIRE: CONDITIONS FOR ACCESS TO A SALARIED EMPLOYMENT - Tanoh, Hilaire (IJRDO - Journal of Social Science and Humanities Research, 2020)
This study analyzes the conditions of access of young women graduates to salaried job in Côte d'Ivoire. The integration of women graduates into the labor market has become increasingly difficult in recent decades. Several factors, including the method of prospecting, initial training and school level, have a particular influence on the quest for job in Côte d'Ivoire. So, what about young women graduates? Our study shows that young women are more interested in literary training than in scientific training. Also, the general school level of these women is lower than that of young men; the largest proportion are the bachelor's degree. Indeed, the number of young women in the workforce is reduced as the school level increases. In addition, young women use recruitment agencies more than social capital to find employment. This study suggests that women should be interested in all scientific and literary training (being versatile), take their studies seriously and extend their time in school in order to reach at least Master in order to facilitate their professional integration. Also, young women graduates must learn to be more professional and competent.